Benzodiazepines and Z-Drug Use among HIV-Infected Patients in Taiwan: A 13-Year Nationwide Cohort Study. (13th January 2015) - Wei, Han-Ting; Chen, Mu-Hong; Wong, Wing-Wai; Chou, Yuan-Hwa; Liou, Ying-Jay; Su, Tung-Ping; Chen, Tzeng-Ji; Bai, Ya-Mei
Abstract : Introduction . Benzodiazepines (BZDs) and zolpidem, zopiclone, and zaleplon (Z-drugs) are commonly prescribed to HIV-infected patients. We hypothesized that frequent BZD and Z-drug use among these patients may be associated with psychiatric illnesses, particularly in long-term users. Methods . We included 1, 081 patients with HIV between 1998 and 2011 from the Taiwan National Health Insurance Research Database and matched them according to age, sex, and comorbidity with uninfected controls to investigate the psychiatric diagnoses and prescriptions of BZDs and Z-drugs. Cumulative defined daily dose (cDDD) was assessed as the indicator of the duration of medication exposure. Patients exhibiting a cDDD exceeding 180 were defined as long-term users. Results . The patients with HIV had an increased risk of any use (odds ratio (OR): 8.70, 95% confidence interval (CI): 6.82–10.97) and long-term use (OR: 5.06, 95% CI: 3.63–7.04) of BZD and Z-drugs compared with those without HIV during the follow-up after demographic data and psychiatric comorbidities were adjusted. Conclusion . A large proportion of the HIV-infected patients received prescriptions of BZDs and Z-drugs. Mood disorders, insomnia, anxiety disorders, HIV infection, and substance use disorder were substantial predictors among the BZD and Z-drug users. These findings suggest that providing psychiatric services for HIV-infected patients is vital.